A framework to support the tourist’s information-needs based on a ubiquitous approach - Carvalho, António (2010)
Nowadays, tourists are increasingly thirsty for information on anything that surrounds him. With the Information Communication Technologies (ICT) evolution that supports the ubiquity, it is necessary to rethink the available models of information and services to tourists. With the evolution of mobile devices, with wireless access, together with the decreasing of the network traffic costs and with the increasing number of access points of wireless access, becomes more common and attractive. Therefore, in this paper we present an analysis of the state of the art of the support applications for tourists for mobile environments, setting them according to the development technologies. In addition, it is also presented a suitable framework to support the tourist’s needs based on a ubiquitous approach.